POLA PEMBERIAN ASI DAN PEMBERIAN MPASI DENGAN STATUS GIZI ANAK USIA 12-23 BULAN - Marwah Aisyah Syahrin; Veni Hadju; Suryani As’Ad (Poltekkes Kemenkes Bandung, 2020)
The weaning foods that do not comply with WHO standards is one of the causes increasing prevalence of malnutrition in children aged 12-24 months. This is descriptive analytic using cross sectional research design. The total population is all mothers who have children aged 12-23 months who are still breastfeeding with sample size is 145 respondents, conducted in the working area of ​​the Polongbangkeng North Puskesmas, Takalar Regency, Makassar City. There was no significant relationship between breastfeeding patterns including giving every number of hours and length of breastfeeding with under two years children nutritional status based on weight / age ( p> 0.05). However, the cross tabulation results show that mothers who breastfeed every 4 hours tend to have poor nutrition and mothers who breastfeed for 5-10 minutes tend to have poor nutrition. There is significant correlation between first weaning foods with nutritional status based on weight / age (p <0.05), cross tabulation which show that the children under 24 months whose weaning foods pattern is given ≥3 times with the appropriate portion according to age and texture and given the first weaning foods at ≥6 months of age tends to have a good nutritional status, while the children under 24 months who has the weaning foods pattern. The first weaning foods are given <3 times with portions that are not appropriate for age and texture that is not suitable and at the age of <6 months tends to have poor nutritional status. The indicator of complementary breastfeeding pattern that was not significantly related to nutritional status based on weight / age was dietary variation (p> 0.05), although the cross tabulation results showed that poor women who were given varied diets tended to have good nutritional status and those who were not given varied foods tended to be less and worse nutritional status.